PELATIHAN PEMBUATAN NATA DE COCO SEBAGAI BENTUK PENERAPAN BIOPRENEUR BAGI SISWA SMA KOTA KEDIRI - rahmawati, ida (Universitas Nusantara PGRI Kediri, 2024)
High schools in Kediri City on average have adequate facilities and laboratory facilities, but entrepreneurial practices based on appropriate technology in the field of Biology are rarely carried out in schools. The city of Kediri has abundant potential for coconut water and the price is affordable, so it can be used as an ingredient for making nata de coco. Training on making nata de coco is considered suitable because it is one of the applications of simple biotechnology at high school level. The aim of the activity is to increase the entrepreneurial interest and enthusiasm of Kediri City High School students based on biology knowledge (biopreneur). Activities begin with the preparation, publication and socialization stages, implementation of training and responses from training participants. The material for making nata de coco was considered to be well received, it was proven that participants were able to carry out the procedure for making nata de coco according to the explanation of the presenter. Teachers and high school students also showed good responses and high enthusiasm, through the many questions regarding the training activities that had been carried out